Process optimization of vegan prebiotic ice cream by response surface methodology - Sakshi K. Devalekar; Iranna S. Udachan (Discover Food)
Abstract The study aimed to optimize the formulation of vegan prebiotic ice cream using coconut milk, date syrup, and fructooligosaccharide (FOS) as key ingredients. Optimization of ice cream formulations was determined by utilizing the Response Surface Methodology. The physico-chemical and sensory properties of the optimized samples were evaluated. According to the findings, ice cream formulation comprising 50% coconut milk, 11.32% date syrup, and 5.81% FOS exhibited the desired quality characteristics. Optimized ice cream's overrun and melting rate was 65.14% and 40.85% respectively. Physico-chemical analysis indicated that the optimized ice cream had higher moisture (66.32%), ash (1.65%), fat content (18.5%), total phenols (79.85 mg GAE/100 ml), and antioxidant activity (54.80) compared to the control, whereas protein (2.93%) and carbohydrate content (10.60%) were lower. The optimized ice cream exhibited a slightly lower pH; adding date syrup affected its color. The developed vegan prebiotic ice cream exhibited favorable attributes such as creaminess, taste, and texture, indicating that it could be a healthy and delicious alternative to dairy ice cream.